Long-Time Asymptotic Behavior of an Integrable Model of the Stimulated Raman Scattering with Periodic Boundary Data - Moskovchenko, E.A.; Kotlyarov, V.P. (Журнал математической физики, анализа, геометрии, 2009)
The long-time asymptotic behavior of the initial-boundary value (IBV) problem in the quarter plane (x > 0, t > 0) for nonlinear integrable equations of the stimulated Raman scattering is studied. Considered is the case of zero initial condition and single-phase boundary data. By using the steepest descent method for oscillatory matrix Riemann{Hilbert problems it is shown that the solution of the IBV problem has different asymptotic behavior in different regions